PREVALENCE AND FACTORS ASSOCIATED WITH POOR PHARMACEUTICAL WASTE DISPOSAL PRACTICES AMONG HOUSEHOLDS IN NANSANA MUNICIPALITY, WAKISO DISTRICT, UGANDA: A CROSS-SECTIONAL STUDY. - LEMBA, HERI; Matovu, Joseph KB; Musoke, David (Student’s Journal of Health Research Africa, 2024)
Introduction The rising demand for pharmaceuticals globally raises concerns about poor disposal of pharmaceutical waste. Pharmaceutical waste lacks clear guidelines for its management, contributing to environmental pollution and high healthcare costs. While some countries implement effective pharmaceutical waste policies, many developing nations including Uganda, face challenges due to insufficient awareness, regulations, and infrastructure. This study determined the prevalence and factors associated with poor pharmaceutical waste disposal practices in Nansana Municipality Wakiso District, Uganda. Methods A cross-sectional study was conducted among 399 households in Nansana Municipality. Stratified sampling was conducted across the four divisions of Nansana Municipality, and a random selection of respondents was made. Data was gathered using a structured questionnaire that included demographics, knowledge, attitudes, and pharmaceutical waste disposal practices. Univariate, bivariate, and multivariable modified Poisson regression analyses identified the prevalence and factors associated with poor pharmaceutical waste disposal. Results The study revealed that 72.2% of Nansana Municipality households used poor pharmaceutical waste disposal, predominantly using toilets (91%). Several factors were significantly associated with poor pharmaceutical waste disposal practices in Nansana Municipality. Respondents aged ≥ 30 years were 1.33 times more likely to engage in poor disposal compared to those aged 20-25 years (APR = 1.33; 95% CI: 1.15-1.54). Household monthly income above USD 137 was linked to a lower likelihood of poor pharmaceutical waste disposal (APR = 0.76; 95% CI: 0.59-0.98). Conclusion The study found a high prevalence of poor pharmaceutical waste disposal in Nansana Municipality, Wakiso District Uganda. Given the influence of age, gender, education, and income on these behaviors, public health strategies must combine educational, economic, and infrastructural measures for effective impact. Recommendation Implementing voluntary take-back programs, enforcing producer responsibility for eco-friendly packaging, and raising public awareness of safe pharmaceutical waste disposal are needed.